2020
DOI: 10.1002/jsfa.10370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of salt levels on the sensory profile and consumer acceptance of Italian dry‐cured ham

Abstract: BACKGROUNDReduction of the salt (NaCl) content in typical Italian dry‐cured ham is intended to reduce sodium dietary intake to meet World Health Organization (WHO) recommendations for the prevention of serious diseases. This reduction is a complex issue because of the multiple roles that salt plays in the product. Hams that were processed to obtain a final product with target salt levels (hams with reduced salt concentration and controls) were analyzed using chemical parameters (salt, moisture, fat, and proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Because of this, sensory analysis are one of the most important methods in judging food quality [ 64 ]. Previous studies [ 52 , 65 , 66 , 67 , 68 , 69 , 70 ] have reported these parameters in ham and indicated the importance of flavor in the overall quality of dry-cured ham. However, the present study is the first to our knowledge to determine the degree of satisfaction of cured ham spiced with saffron.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, sensory analysis are one of the most important methods in judging food quality [ 64 ]. Previous studies [ 52 , 65 , 66 , 67 , 68 , 69 , 70 ] have reported these parameters in ham and indicated the importance of flavor in the overall quality of dry-cured ham. However, the present study is the first to our knowledge to determine the degree of satisfaction of cured ham spiced with saffron.…”
Section: Discussionmentioning
confidence: 99%
“…This division indicates how important the role of salt is in the processing of meat into meat products. Salt also has a role in proteolytic enzymes inhibition [ 32 , 45 , 46 , 47 ].…”
Section: Sodium Occurrence In Foods and Possibilities Of Its Reductionmentioning
confidence: 99%
“…Higher temperature and salt reduction positively affected flavour formation, increased proteolysis and free amino acids content. Salt influenced proteolytic enzymes inhibition; therefore, in reduced-salt meat products, an increase in the proteolytic index was observed [ 47 , 131 ]. To reach the same safety condition of the reduced-salt dry-cured Italian ham, the cold-drying period was prolonged.…”
Section: Salt Content Reduction and Its Consequencesmentioning
confidence: 99%
“…Fellendorf et al [ 61 ] reported that 60% of salt could be reduced without any impact on the sensory effects, except for saltiness. For dry-cured ham, the decreased salt content was found to have a significant effect on redness, marbling, saltiness, hardness, fibrousness, and overall quality [ 66 ]. However, consumer liking of reduced-salt dry-cured ham was higher than that of the control; this is because consumers have expressed that reduced-salt dry-cured ham was healthier than the control.…”
Section: Strategies To Improve the Sensory Properties Of Reduced-salt Meat Productmentioning
confidence: 99%